2022
DOI: 10.1080/00207543.2022.2104180
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement learning applied to production planning and control

Abstract: The objective of this paper is to examine the use and applications of reinforcement learning (RL) techniques in the production planning and control (PPC) field addressing the following PPC areas: facility resource planning, capacity planning, purchase and supply management, production scheduling and inventory management. The main RL characteristics, such as method, context, states, actions, reward and highlights, were analysed. The considered number of agents, applications and RL software tools, specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 59 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…The authors analyzed 264 different publications between 2013 and October 2022 and found, that optimizing energy consumption as well as costs and reducing reliance on expert knowledge as the main objectives of these applications. Esteso et al [15] came to similar conclusions and add that the great majority of RL applications in production technology utilize simplified (virtual) environments with discrete action spaces. Panzer and Bender [16] also conducted a literature review and conclude that in numerous applications RL outperforms previously used heuristics or algorithms.…”
Section: Reinforcement Learning For Process Optimizationmentioning
confidence: 67%
“…The authors analyzed 264 different publications between 2013 and October 2022 and found, that optimizing energy consumption as well as costs and reducing reliance on expert knowledge as the main objectives of these applications. Esteso et al [15] came to similar conclusions and add that the great majority of RL applications in production technology utilize simplified (virtual) environments with discrete action spaces. Panzer and Bender [16] also conducted a literature review and conclude that in numerous applications RL outperforms previously used heuristics or algorithms.…”
Section: Reinforcement Learning For Process Optimizationmentioning
confidence: 67%
“…These algorithms, ranked from most to least frequently employed, include Qlearning, temporal difference TD(λ) algorithm, SARSA, ARL, informed Q-learning, dual Q-learning, approximate Q-learning, gradient descent TD(λ) algorithm, revenue sharing, Q-III learning, relational RL, relaxed SMART, and TD(λ)-learning. In the field of DRL, many value-based approaches have been employed, such as DQN (Deep Q-Learning Networks), loosely-coupled DRL, multiclass DQN, and the Q-network algorithm [48][49][50][51][52][53][54][55][56][57][58].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The machine learning approach RL is similar to human trial-and-error learning [3]. In an industrial open-die forging plant, this learning procedure runs unconsciously.…”
Section: Previous Reinforcement Learning In Open-die Forgingmentioning
confidence: 99%
“…In this publication, a novel approach for the design of optimized open-die forging processes using the machine learning method reinforcement learning (RL) is presented. RL algorithms as well as deep reinforcement learning (DRL) approaches have been successfully applied in various manufacturing applications including metal forming for different process design and control tasks [3,4]. Gamal et al [5] trained a deep deterministic policy gradient algorithm to control the roll gap in bar and wire hot rolling using real plant measurement data.…”
Section: Introductionmentioning
confidence: 99%